USER EXPERIENCE ANALYSIS OF AN E-COMMERCE WEBSITE USING USER EXPERIENCE QUESTIONNAIRE (UEQ) FRAMEWORK - Kevin Andika Lukita; Maulahikmah Galinium; James Purnama (Lembaga Penelitian Universitas Trisakti, 2018)
The purpose of this study is to find the attribute of the Nappa Milano onlinestore that needs improvement the most based on the result of the userexperience (UX) evaluation of the customers of Nappa Milano online store.Nappa Milano is a brand of male footwear that has been since 2013. This studyuses the UEQ framework to conduct the UX evaluation. There are severalattribute a website has which is the attractiveness, perspicuity, efficiency,dependability, stimulation, and Novelty. The result indicates that thePerspicuity attribute is the attribute that receives the most positive evaluationbecause it receives the score of 2.048 from the scale which ranges from -3 to 3.On the other hand, the novelty attribute is the attribute of the Nappa Milanoonline store that needs most improvement because it receives the mostnegative evaluation because it receives the score of 0.157 from the scale whichranges from -3 to 3.